The Influence of Workload, Burnout and Job Satisfaction on the Performance of Investigants in the Coordination and Supervision Function of Civil Servant Investigates (korwas PPNS) - Etty Wachyuni; Sugeng Suroso; Supardi Supardi (Dinasti International Journal of Management Science, 2023)
In every organization, performance is important in determining how an organization progresses, to know whether the organization is moving forward or backward, or aims to achieve organizational goals. Individuals have high expectations of their organizational work, they want to develop and look for opportunities to realize their potential.The research method used in this research is quantitative with a survey approach to find out and see the effect of workload, burnout and job satisfaction on performance. The research sample was 134 peopleactive and passive personnel in an PPNS Korwas organization. Data collection using survey techniques. Data analysis in this study used the SPSS method with multiple linear regression tests. Research resultsthat the independent variable Workload partially has an influence on performance. Burnout independent variable partially and has no significant effect on performance. independent variable Job satisfaction partially and has a significant effect on performance.